GRAMMATICAL INTRICACY AND LEXICAL DENSITY OF READING TEXTS OF ENGLISH TEXTBOOK FOR SENIOR HIGH SCHOOL GRADE XII - Johannes Jefria Gultom; Evrianto Pintubatu (Universitas Negeri Medan, 2022)
ABSTRACTThis study deals with the grammatical intricacy and lexical density of reading texts of English textbook for senior high school students grade XII. The objectives of this study are to investigate the level of grammatical intricacy (GI), and lexical density (LD) of the reading texts of English Textbook. This study was conducted by using descriptive qualitative and content analysis design. The data of this study were simple clauses, clauses complexes, sentences, lexical items and content carrying lexical items (nouns, verbs, adjectives and adverbs) of the English reading texts of Look Ahead 3, English textbook for senior high school grade XII published by Erlangga 2007. The result of the analysis showed that: (1).The level of grammatical intricacy of four out of six reading texts is high (3.53, 2.3, 2.71, and 2.25) and the other two texts are medium (2) and low (1.83). (2).The level of lexical density of four out of six reading texts are low (42.67%, 45.93%, 48.47%, and 36.99%) and the other two texts are high (58.36, and 55.40%). Keywords: grammatical intricacy; lexical density; reading texts